Studi Motivasi Belajar Siswa Kelas V Pengguna Media Sosial Tiktok Di SDN Simomulyo I Surabaya: Indonesia - Azizul Hakim, M. Wandi; Muslimin Ibrahim; Syamsul Ghufron; Akhwani (FKIP, Universitas Palangka Raya, 2024)
This research is motivated by the rise of elementary school students who participate in playing TikTok which is feared will affect their learning motivation. The purpose of this study was to determine the intensity level of fifth grade students in playing TikTok, the learning motivation of fifth grade students using social media TikTok, and the correlation between the intensity of using TikTok and students' learning motivation. This research includes observational research. The data collection technique uses the interview method, distributing questionnaires on student learning motivation, and correlations between the intensity of using TikTok and learning motivation. The results showed that the use of TikTok social media for fifth grade students spent 2 hours 58 minutes in one day, student learning motivation achieved a score of 3.22 which was included in the fairly good category, and the correlation obtained a score of -0.16 which was included in the very low category. So it doesn't really affect student learning motivation because students play TikTok outside of their study time.